Integration of Fire Risk in a Sustainable Forest Management Model - Costas Freitas, M.B. (2018)
In Mediterranean areas, forest fires are a considerable risk most years. The seasonality of the climate with a dry summer, high temperatures and low rainfall (which implies increased flammability of materials) is one of the main factors in the ignition and progression of fires. This factor conjugated with more favourable biophysical conditions (e.g., high slopes, aspect) leads to easy propagation and the increasingly destructive power of such phenomena. To prevent and reduce the consequences of forest fires, it is necessary to simulate and forecast the territory use and management, not only focused on forest areas, but also on all land uses and agricultural activities that may coexist there, considering the probability of fire occurrence. The objective of this paper is to present a methodological approach to address the integration of fire risk in integrated Mediterranean forest management models. The methodological approach considers simultaneously the climatic conditions through different times of the year (more or less favourable to forest fire damage) and structural conditions addressed to land uses, aspect, slope, roads and demographic density. The methodological approach was implemented in a management area located in the Algarve, in southern Portugal. The results for the Algarve region showed that the proposed approach is very useful for managers, since it allowed the calculation of fire susceptibility, vulnerability and fire damage, according to several climatic scenarios. It also allowed the incorporation of different paths regarding different fire risk conditions and the minimization of risk due to fire damage through different management responses.